Society of Workers’ Housing Estates and its attempt to overcome the residential crisis in interwar Poland: A contribution to further research - Frejtag, Jakub (Budownictwo i Architektura / Civil and Architectural Engineering, 2021)
After the Great War, one of the most challenging obstacles of the newly recreated Polish state was to ensure residential space for the group of citizens most vulnerable to exclusion. Labourers indeed required an inexpensive and modest habitations maintaining modern sanitary standards. Such facilities were underrepresented in Poland at that time. Mostly overpriced and unsanitary flats were offered in 19th-century housing. Also new housing, although with all modern amenities, did not provide flats with parameters that could meet the expectations of the least wealthy of labourers. In such circumstances, at the end of 1934, a new state-owned company was created – the Society of Workers’ Housing Estate (Towarzystwo Osiedli Robotniczych). Its aim was to build and grant loans for the construction of residential areas with flats meeting the needs of the lower-class labourers. Despite the difficulties, up to 1939, thousands of new flats were built under the Society’s initiative. All these investments exemplify a successful and far-reaching social policy of Second Polish Republic that made residential crisis manageable.